User-Generated Content and Cultural Public Relations Approach to the Virtual Branding of Lombok Tourism - Nur'aeni Tarmidzi; Dasrun Hidayat; Zikri Fachrul Nurhadi; Reza Rizkina Taufik (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Information about tourist attractions is the right of tourists protected by tourism laws and consumer protection. One approach used to fulfill consumer information is through User Generated Content (UGC). This approach serves as virtual branding activities to promote tourist attractions. The content presented must be able to attract visitors' interest. Therefore, there needs to be an effort by tourism managers to provide facilities and tourism infrastructure to ensure visitor comfort. The experiences of tourists will become content published on social media or applications used in User Generated Content (UGC) activities. The purpose of this research is to analyze the motives behind visitors' communal experiences and to analyze the challenges faced by tourism managers in dealing with User Generated Content (UGC) activities. This study uses a qualitative method with a phenomenological approach. The results obtained indicate that the main motive consciously and collectively built for UGC is to share useful information about tourist attractions through citizen journalism activities. Other results show that the challenges faced by tourism managers in dealing with UGC activities include enhancing facilities, improving tourism accessibility, and increasing cooperation to generate more UGC content by actively involving the community through local activities. One successful example of cooperation is through empowering local residents in the traditional weaving handicraft activities typical of Lombok, which are part of the Micro, Small, and Medium Enterprises (MSMEs).